Optic Neuritis as Isolated Manifestation of Leptomeningeal Carcinomatosis: A Case Report and Systematic Review of Ocular Manifestations of Neoplastic Meningitis - Silvia Lanfranconi; Paola Basilico; Ilaria Trezzi; Linda Borellini; Giulia Franco; Vittorio Civelli; Francesco Pallotti; Nereo Bresolin; Pierluigi Baron (Neurology Research International)
Introduction. Leptomeningeal carcinomatosis occurs in about 5% of cancer patients. Ocular involvement is a common clinical manifestation and often the presenting clinical feature. Materials and Methods. We report the case of a 52-year old lady with optic neuritis as isolated manifestation of neoplastic meningitis and a review of ocular involvement in neoplastic meningitis. Ocular symptoms were the presenting clinical feature in 34 patients (83%) out of 41 included in our review, the unique manifestation of meningeal carcinomatosis in 3 patients (7%). Visual loss was the presenting clinical manifestation in 17 patients (50%) and was the most common ocular symptom (70%). Other ocular signs were diplopia, ptosis, papilledema, anisocoria, exophthalmos, orbital pain, scotomas, hemianopsia, and nystagmus. Associated clinical symptoms were headache, altered consciousness, meningism, limb weakness, ataxia, dizziness, seizures, and other cranial nerves involvement. All patients except five underwent CSF examination which was normal in 1 patient, pleocytosis was found in 11 patients, increased protein levels were observed in 16 patients, and decreased glucose levels were found in 8 patients. Cytology was positive in 29 patients (76%). Conclusion. Meningeal carcinomatosis should be considered in patients with ocular symptoms even in the absence of other suggestive clinical symptoms.